POTENSI DUSUN NGALIAN SEBAGAI DAYA TARIK WISATA EDUKASI DI KELURAHAN WIDODOMARTANI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Ismaya, Dhea Riski; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This study aims to describe the potential of educational tourism that can be used as a tourist attraction as the first step of tourism development in Ngalian Village. This research uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, literature studies, and documentation studies. The analysis was carried out with the 4A's tourism product component approach and the research instrument was an interview with Ngalian Village stakeholders. The problems raised in this study are what are the potential attractions of educational tourism in Ngalian Village and what kind of community participation in the educational tourism program in Ngalian Village, Widodomartani. The results of this study indicate that (1) Ngalian village can already be categorized as an educational tourism village because there are tourist attractions that contain high educational value. Tourist attractions or tourist attractions in Ngalian village consist of natural attractions, artificial tourism, cultural tourism and culinary tourism. These educational tourism attractions are then classified into 4 types of educational tourism, namely sciences educational tourism, sports educational tourism, cultural educational tourism and agro-tourism. The identification of tourism development through the 4A's approach in implementation is very good, this is evident from the increasing tourist visits and the ability of the community to manage tourism activities in Ngalian village. (2) The Ngalian village community has a high role in participating in the educational tourism program in Ngalian village. This form of participation in its implementation can be seen from mental and emotional involvement, willingness to give something and a sense of responsibility. Keywords: Tourism potential, Tourism Attraction, Edutourism, Participation